"Birtherism" and Anti-Blackness: The Anti-Islamic Ante-Life of Africanized Slavery. Issue 8 (17th November 2017) - Grimes, Katie Walker
Abstract : The first black President of the United States, Barack Obama, entered office on a wave of racial optimism. But rather than transcending the United States' racialized history, Obama's presidency has in a sense "outed" it, exposing this history's anti-Islamic origins. This article establishes a link between anti-blackness and the Islamophobic reaction to his election: late medieval and early modern European Christians could classify newly Africanized peoples as uniquely and ontologically enslaveable only because they previously had imagined Muslims as such.